Digital dynamism: How IT and social media are enhancing business opportunities for Sri Lankan entrepreneurs - Anushka Wijesinha (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2015)
As the Sri Lankan economy attempts to transform into a more value-added and knowledge-led one, recent advancements in technology and innovation have created a plethora of new opportunities for small and medium-sized enterprises. This paper provides four case studies of innovative enterprises and initiatives to demonstrate how the digital economy is enhancing the country's business potential and creating jobs. The firms studied are all start-ups run by young professionals (between 28-35 years) and are specifically unique to show the range of possible benefits. The aim of this initiative is to shape a new narrative around the use of IT and social media for entrepreneurship in the future.
Keywords: M13; M15; M21; M37; O31; O33; 330; competitiveness; entrepreneurship; innovation; SMEs; technology